MCDHF calculations of isotope shifts in neutral antimony. (October 2018) - Gamrath, S.; Palmeri, P.; Quinet, P.; Bouazza, S.; Godefroid, M.
Highlights: Ab initio fully relativistic MCDHF calculations of isotope shift electronic parameters have been carried in neutral antimony. Relativistic normal mass shift, specific mass shift and field shift electronic parameters are given for all the known fine-structure levels belonging to the even 5 p 2 6 s J = 1 / 2 − 3 / 2 and the odd 5 p 3 + 5 p 2 6 p + 5 p 2 7 p J = 1 / 2 − 5 / 2 configurations of Sb I and for E1 transitions involving them. Comparison with the two sets of experimental line isotope shifts shows [4, 5] a good agreement with our MCDHF predictions for the most recent measurements by Sobolewski et al. [5] but does not allows us to reject the old values of Buchholz et al. [4] for 5 p 3 − 5 p 2 6 s, although striking differences are seen, due to the large uncertainty affecting the change in mean-square nuclear radius between the two stable isotopes [3] . Abstract: Ab initio multiconfiguration Dirac–Hartree–Fock (MCDHF) calculations have been carried out in order to determine the isotope shift (IS) electronic parameters of transitions belonging to electric dipole (E1) transition arrays 5 s 2 5 p 3 − 5 s 2 5 p 2 6 s, 5 s 2 5 p 2 6 s − 5 s 2 5 p 2 6 p and 5 s 2 5 p 2 6 s − 5 s 2 5 p 2 7 p in neutral antimony, Sb I. In a correlation model limited to single and double excitations from the valence shells, these parameters, combined with the changes in mean-square nuclear charge radius δ ⟨ r 2 ⟩ 123, 121 compiled by Angeli and Marinova [3] produce isotope shifts values in good agreement with the most recent measurements by high-resolution emission and optogalvanic absorption spectroscopy of Sobolewski et al. [5] but not with the old measurements of Buchholz et al. [4] for 5 p 3 − 5 p 2 6 s . However, our analysis does not allow to reject the latter due to the large uncertainty affecting δ ⟨ r 2 ⟩ 123, 121, i.e. 0.072 ± 0.048 fm 2 [3]. This shows the need of a more accurate determination of this nuclear parameter. Although improving excitation energies, the inclusion of core-valence correlation limited to one hole in the 4d core subshell destroyed the theory-experiment agreement on the IS parameters.